The Relationship Between Rheumatoid Arthritis and Serum Vitamin D Concentrations - Muhammad Afzal, Zaid Aslam, Ali Umair, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to determine the association between rheumatoid arthritis and serum vitamin D levels. Study Design: Case-control study Place and Duration: THQ Hospital Kamalia. Aug 2021-Jan 2022 Methods: There were one hundred and sixty patients were presented in this study. After obtaining informed written permission, we took detailed demographic information on all patients who had signed up for treatment. Clinical signs and symptoms, X-ray findings, and anti-citrullinated protein levels more than 20 u/mL were all used to diagnose RA in this patient's instance. They all pointed to the disease. Group I featured 80 people with verified rheumatoid arthritis, whereas group II had 80 individuals who did not have rheumatoid arthritis. The levels of vitamin D in both groups' blood were compared. Data was analysed using SPSS 2.0. Results: There were 45 (56.3%) males and 35 (43.7%) females in group I and in group II 42 (52.5%) males and 38 (47.5%) females. Mean age in group I was 44.7±8.35 years and had mean BMI 27.8±9.45 kg/m2 while in group II mean age was 46.5±6.51 years with mean BMI 28.6±6.51 kg/m2. Hypertension and diabetes were the most common comorbidities. Vitamin D level in group I was significantly lower 29.41±5.59 as compared to group II 40.41±8.81(ng/mL). Among 80 cases of rheumatoid arhthritis, positive patients for rheumatoid factor were 72 (90%) in which frequency of hypovitaminos was found among 65 (90.3%) cases. Conclusion: People with RA are far more likely to be vitamin D deficient, and the severity of the disease is directly correlated with this insufficiency. Since vitamin D deficiency affects women more than males, they should be tested with a high degree of suspicion. Taking vitamin D supplements may be necessary to prevent or reverse the progression of the disease.